2021
DOI: 10.1177/19386400211029130
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Posttraumatic Medial Growth Arrest of the Distal Tibia in Adolescents

Abstract: Background Partial growth arrest of the medial part of the distal tibial physis following fractures that penetrated the epiphysis is relatively common. We present the results of treatment, based on a protocol of supramalleolar tibial and fibular osteotomy for ankle alignment correction, and contralateral epiphysiodesis of distal tibia and fibula to balance leg length discrepancy (LLD). Methods This case series study describes the results of 7 patients with a median age of 14 years (range = 10-15 years) who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In this study, we confirmed that SMOT is equally good in correcting TAVD in adolescents, and we chose open medial wedge osteotomy over closed medial wedge osteotomy because it does not lead to shortening of the tibia in developing adolescents and the simple surgical approach makes it easier to accurately osteotomize the bone [ 23 ]. Our results showed that the mean preoperative TAS improved from 61.53 ± 3.74° in 32 patients to 88 ± 1.72° at 12 months postoperatively, the mean preoperative TT decreased from 2.25 ± 1.32° to 0.5 ± 0.57° at 12 months postoperatively, the mean preoperative TLS improved from 76.72 ± 0.21° to 79.34 ± 1.52° at 12 months postoperatively, all the radiographic outcomes were significantly improved, the mean preoperative AOFAS score improved from 65.5 ± 9.40 to 92.34 ± 4.00, the mean preoperative VAS score decreased from 2.44 ± 1.24 to 0.78 ± 0.75 at 12 months postoperatively, and the mean preoperative ROM of ankle improved from 50.16 ± 7.46 to 55.78 ± 4.77 at 12 months postoperatively, all of which were also significant improvements in clinical outcomes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, we confirmed that SMOT is equally good in correcting TAVD in adolescents, and we chose open medial wedge osteotomy over closed medial wedge osteotomy because it does not lead to shortening of the tibia in developing adolescents and the simple surgical approach makes it easier to accurately osteotomize the bone [ 23 ]. Our results showed that the mean preoperative TAS improved from 61.53 ± 3.74° in 32 patients to 88 ± 1.72° at 12 months postoperatively, the mean preoperative TT decreased from 2.25 ± 1.32° to 0.5 ± 0.57° at 12 months postoperatively, the mean preoperative TLS improved from 76.72 ± 0.21° to 79.34 ± 1.52° at 12 months postoperatively, all the radiographic outcomes were significantly improved, the mean preoperative AOFAS score improved from 65.5 ± 9.40 to 92.34 ± 4.00, the mean preoperative VAS score decreased from 2.44 ± 1.24 to 0.78 ± 0.75 at 12 months postoperatively, and the mean preoperative ROM of ankle improved from 50.16 ± 7.46 to 55.78 ± 4.77 at 12 months postoperatively, all of which were also significant improvements in clinical outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been studied in much younger patients. Kotlarsky et al [ 23 ] performed supra-ankle osteotomy in seven patients with traumatic ankle varus deformity at a median age of 14 years (10–15 years), and the results demonstrated that SMOT can safely and effectively correct adolescent ankle varus deformity, and provided an anatomical correction of post-traumatic distal tibial varus deformity and restored ankle joint alignment. However, the number of patients included was limited, so more patients are needed to enrich the findings.…”
Section: Discussionmentioning
confidence: 99%